2022
DOI: 10.1186/s12883-022-02577-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of background EEG activity in juvenile myoclonic epilepsy during valproic acid treatment: a standardized, low-resolution, brain electromagnetic tomography (sLORETA) study

Abstract: Background By definition, the background EEG is normal in juvenile myoclonic epilepsy (JME) patients and not accompanied by other developmental and cognitive problems. However, some recent studies using quantitative EEG (qEEG) reported abnormal changes in the background activity. QEEG investigation in patients undergoing anticonvulsant treatment might be a useful approach to explore the electrophysiology and anticonvulsant effects in JME. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…VA had a variable impact on spike frequency, reducing the frequency by over 50% in 57% of the tested mice, with a smaller effect in 28% of the mice, and increased spike frequency in one mouse (Figure 2B-C). Focusing on quantitative analyses of background activity, VA reduced the total power spectral density (PSD) in all the tested DS mice (Figure 2D-F), in agreement with previous reports in humans 14,15 . When inspecting the relative power of each frequency band, we observed an increase in the contribution of the beta band (Figure 2G).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…VA had a variable impact on spike frequency, reducing the frequency by over 50% in 57% of the tested mice, with a smaller effect in 28% of the mice, and increased spike frequency in one mouse (Figure 2B-C). Focusing on quantitative analyses of background activity, VA reduced the total power spectral density (PSD) in all the tested DS mice (Figure 2D-F), in agreement with previous reports in humans 14,15 . When inspecting the relative power of each frequency band, we observed an increase in the contribution of the beta band (Figure 2G).…”
Section: Resultssupporting
confidence: 90%
“…The effect of ASMs on background EEG activity was studied before, but not in Dravet. VA was shown to reduce the power of background EEG in patients with idiopathic generalized epilepsy, and juvenile myoclonic epilepsy 14,15 , and CLB caused spectral changes in rabbits 16 and kindled rats 17 .…”
mentioning
confidence: 99%
“…VA had a variable impact on spike frequency, reducing the frequency by over 50% in 57% of the tested mice, with a smaller effect in 28% of the mice, and increased spike frequency in one mouse ( Figures 2B, C ). Focusing on quantitative analyses of background activity, VA reduced the total power spectral density (PSD) in all the tested DS mice ( Figures 2D–F ), in agreement with previous reports in humans ( Clemens et al, 2006 ; Moon et al, 2022 ). When inspecting the relative power of each frequency band, we observed an increase in the contribution of the beta band ( Figure 2G ).…”
Section: Resultssupporting
confidence: 90%
“…The effect of ASMs on background EEG activity was studied before, but not in Dravet. VA was shown to reduce the power of background EEG in patients with idiopathic generalized epilepsy, and juvenile myoclonic epilepsy ( Clemens et al, 2006 ; Moon et al, 2022 ), and CLB caused spectral changes in rabbits ( Gerhards, 1978 ) and kindled rats ( Harris et al, 1988 ). Here, utilizing DS mice ( Scn1a A1783V/WT ) we show that acute administration of Dravet-recommended drugs, VA, CLB, a combination of CLB + STP, or STP alone, was associated with a reduction in the frequency of interictal spikes in most of the tested mice, along with a significant increase in relative beta band contribution to the total power.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we recently published another study that investigated background EEG changes before and after anticonvulsant treatments in JME. [ 32 ] In that study, focal features of EEG were observed by the source localization method, but various cortical regions including the frontal, parietal, occipital, and limbic lobes were also involved. The results were consistent with this study, suggesting that JME is distinct from focal epilepsies.…”
Section: Discussionmentioning
confidence: 98%